Effect of orlistat on liver fat content in patients with nonalcoholic fatty liver disease with obesity: assessment using magnetic resonance imaging-derived proton density fat fraction. (September 2019) - Ye, Junzhao; Wu, Yanqin; Li, Fuxi; Wu, Tingfeng; Shao, Congxiang; Lin, Yansong; Wang, Wei; Feng, Shiting; Zhong, Bihui
Background: The liver effect of orlistat as a weight control treatment in patients with nonalcoholic fatty liver disease (NAFLD) with obesity remains undetermined. This study quantified liver fat improvement by orlistat in a Chinese cohort with NAFLD accompanied by obesity, diagnosed by a lower body mass index threshold than that for White patients. Materials and methods: We conducted a parallel-group, open-label, 24-week, randomized clinical trial registered at the Chinese Clinical Trial Registry (ChiCTR-IPR-17012258). Obese participants with NAFLD were randomized 1:1.5 to the intervention group with orlistat or conventional care. Liver fat quantification was assessed by magnetic resonance imaging-based proton density fat fraction with Dixon sequence. Results: Overall, 170 ( n = 68, orlistat 120 mg three times/day and n = 102, conventional therapy) and 130 patients with NAFLD ( n = 56, orlistat and n = 74, conventional therapy) were included for intention-to-treat (ITT) and per-protocol (PP) analysis, respectively. Orlistat reduced liver fat content to a greater degree than conventional care [−5.45% versus −1.96%, p < 0.001 (ITT analysis) and −6.66% versus −2.68%, p < 0.001 (PP analysis)]. The 6-month rate of decrease in steatosis grades was higher in the orlistat group [45.6% versus 22.5% (ITT analysis), 57.4% versus 30.3% (PP analysis), both p < 0.001]. Multivariate logistic regression analysis identified orlistat treatment [odds ratio (OR) = 2.4; 95% confidence interval (CI) 1.1–5.6, p = 0.036] as an independent predictor of steatosis improvement. Among patients with orlistat therapy, weight loss (OR = 1.2, 95% CI 1.1–1.4, p = 0.040) and severe steatosis (OR = 6.7, 95% CI: 1.1–40.3, p = 0.03) remained predictive of steatosis improvement. Conclusions: Orlistat can effectively promote steatosis improvement and may serve as a treatment option for controlling NAFLD. Chinese Clinical Trial Registry identifier: ChiCTR-IPR-17012258